Visualisation of User Stories to UML use Case Diagram - Mohammad Nazrul, Mornie; Nurfauza, Jali; Cheah, Wai Shiang; Edwin, Mit; Suhaila, Saee; Suriati Khartini, Jali; Desmond, Greer (Semarak Ilmu Publishing, 2026)
The growing usage of Agile methodology in software development projects among industry professionals (software engineers, system analysts, requirement engineers, etc.) and academia (software engineering students) leads to the need for the implementation of UML diagram for requirements modelling. Use case diagram, an example of UML diagram, is a very powerful tool to model the requirements specified by the users while also helping the development teams understand the functionalities and interactions between users and the system. However, there is a lack of a system or tool that can perform the operation to visualise the use case diagram directly from user stories because generating this diagram manually requires a deep understanding of the requirements and effective communications with stakeholders and it consume lots of time while previous studies which relate to this study are unable to fulfil the relationship elements of use case diagram. This study will introduce a method to visualise the use case diagram from structured textual user stories by utilising Natural Language Processing (NLP) and application of logical rules which will be done in four stages, namely Requirement Gathering, Natural Language Processing, Application of Logical Rules and UML Diagram Generation. A tool named Stanford CoreNLP will be used to perform four techniques of NLP: tokenisation, stemming and lemmatisation, POS tagging and dependency parsing to process the textual user stories, followed by applying the logical rules before generating the use case diagram. This study will propose a method to solve the gap, which is the problem with the generation of relationship elements, while contribute a semi-automated approach to generate a use case diagram from user stories.